Enhancement higher order thinking skills in algebra by The PINTER mathematics learning model. (April 2020) - Kurniawan, Heru; Budiyono,; Sajidan,; Siswandari,
Abstract: This study aims to determine the enhancement of students' high-level thinking skills in algebra material through the application of the PINTER mathematics learning model. The PINTER mathematics learning model was developed with the learning stages: Presentation to real life, Investigation, Team Activities, Explanation & Reasoning, and Reinforcement. This research instrument uses tests to determine the effectiveness of learning, observation to see the feasibility of the model, practicality questionnaires to determine whether the model is easy to apply, Practicality questionnaires to determine whether the model is easy to apply, and student questionnaire responses to determine student responses to the learning process. This research was conducted in 4 Junior High School (SMP) in Purworejo Regency. The stages of the study were carried out in 5 meetings where each meeting was reflected and corrected to be carried out at the next meeting. Research results show: 1) The PINTER mathematics learning model is effective for improving students' high-level thinking skills on algebra material, 2) The PINTER mathematics learning model is practically or easy to apply by teachers, 3) the PINTER mathematics learning model gets good responses from students. Thus, PINTER's mathematics learning model has the potential to be applied to mathematics learning, especially in efforts to enhance higher-order thinking skills.